2006
DOI: 10.1038/nature04381
|View full text |Cite
|
Sign up to set email alerts
|

Distinct memory traces for two visual features in the Drosophila brain

Abstract: The fly Drosophila melanogaster can discriminate and remember visual landmarks. It analyses selected parts of its visual environment according to a small number of pattern parameters such as size, colour or contour orientation, and stores particular parameter values. Like humans, flies recognize patterns independently of the retinal position during acquisition of the pattern (translation invariance). Here we show that the central-most part of the fly brain, the fan-shaped body, contains parts of a network medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
411
3
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 390 publications
(433 citation statements)
references
References 33 publications
13
411
3
1
Order By: Relevance
“…Output from the MB α′β′ neurons and EB neurons have been implicated in olfactory memory consolidation and visual pattern memory (23,(49)(50)(51)(52)(53). Because activity of dopamine neurons and MB α′β′ neurons are required for both oviposition preference for ethanol and ethanol-reward memory in the fly (23), our results raise the possibility that competing dopamine responses may also modulate memory for ethanol reward.…”
Section: Discussionmentioning
confidence: 69%
“…Output from the MB α′β′ neurons and EB neurons have been implicated in olfactory memory consolidation and visual pattern memory (23,(49)(50)(51)(52)(53). Because activity of dopamine neurons and MB α′β′ neurons are required for both oviposition preference for ethanol and ethanol-reward memory in the fly (23), our results raise the possibility that competing dopamine responses may also modulate memory for ethanol reward.…”
Section: Discussionmentioning
confidence: 69%
“…Whereas sensory neuron function was essential for the rhythmic crawling, larvae immobilized by exposure to 37°C still exhibited movements of the mouth hook (SI Movie 3), indicating that some other type of movement remains. To corroborate these results, we used Gal80 ts /UAS-inwardly rectifying K ϩ channel (Kir) as an alternative means to silence all sensory neurons conditionally at third larval instar by acutely overexpressing Kir so that the neurons would be much less excitable (19). We found that larvae carrying both SN-Gal4 and Gal80 ts /UAS-Kir became immobilized after exposure to restrictive temperature for 30 min (data not shown).…”
Section: Drosophila Larval Sensory Neurons Are Necessary For Locomotionmentioning
confidence: 75%
“…The strong expression of dNR2 in ellipsoid body interested us, as another closely-related substructure of the central complex, the fanshaped body, appears to subserve a short-term memory trace for visual learning 25 and may be involved with LTM formation after courtship conditioning 26 . We identified several GAL4 drivers with preferential expression in these dNR2-positive ellipsoid body neurons ( Fig.…”
Section: Resultsmentioning
confidence: 96%